2019
DOI: 10.3389/fimmu.2019.00731
|View full text |Cite
|
Sign up to set email alerts
|

DHAV-1 Inhibits Type I Interferon Signaling to Assist Viral Adaption by Increasing the Expression of SOCS3

Abstract: Duck hepatitis A virus type 1 (DHAV-1) is one of the most lethal pathogens in the duck industry. The attenuated vaccine (the CH60 strain) is cultivated through serial passage in chicken embryos and is widely used for the prevention and control of the disease. However, the specific mechanism underlying its adaptation in chicken embryos has not been fully elucidated. In this study, we first infected chicken embryo fibroblasts (CEFs) with the DHAV-1 CH60 strain. The peak of viral proliferation occurred within 36–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…On the other hand, in the present study, one upregualted mRNA (SOCS3), potentially trans-regulated by 32 lncRNAs (Additional file 5: Data S5), was also found to be upregulated during infection with Duck hepatitis A virus type 1 (DHAV-1). Overexpression of SOCS3 significantly inhibited the expression of IFNα, and indirectly decreased the expression of the antiviral proteins MX1 and OASL through inhibiting Janus kinase (JAK)-STAT signaling pathway, thus ultimately promoting viral proliferation and assisting in viral adaptation of DHAV-1 in chicken embryos [118]. However, SOCS3 overexpression could promote the expression of IFN-γ, and the IFN-γ has been found to play a critical role in host defense against E. tenella infection [119,120].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the present study, one upregualted mRNA (SOCS3), potentially trans-regulated by 32 lncRNAs (Additional file 5: Data S5), was also found to be upregulated during infection with Duck hepatitis A virus type 1 (DHAV-1). Overexpression of SOCS3 significantly inhibited the expression of IFNα, and indirectly decreased the expression of the antiviral proteins MX1 and OASL through inhibiting Janus kinase (JAK)-STAT signaling pathway, thus ultimately promoting viral proliferation and assisting in viral adaptation of DHAV-1 in chicken embryos [118]. However, SOCS3 overexpression could promote the expression of IFN-γ, and the IFN-γ has been found to play a critical role in host defense against E. tenella infection [119,120].…”
Section: Discussionmentioning
confidence: 99%
“…Also, SOCS3 is a host protein that can be employed by viruses. SOCS3 can be induced by various viruses, including NDV, DHAV-1, HIV-1 and Enterovirus 71 (EV71) (Akhtar et al, 2010;Wang et al, 2019a;Xie et al, 2019;Gao et al, 2020). SOCS3 also inhibits or promotes viral replication when acted upon by small RNA molecules (Ma et al, 2018;Wang et al, 2019b;Duan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been recently reported that the differences in immune responses correlate with viral attenuation [21]. After serial passages in embryonated chicken eggs, the attenuated strain of DHAV-1 was able to damage the type I IFN response and thereby promote viral propagation [36].…”
Section: Discussionmentioning
confidence: 99%